(untitled) (Dhaka University Journal of Science, 2022)
Globally, scrap tyres are increasing due to the increased number of vehicles. In contrast, in the recent years, alternatives to fossil fuels are exploring to overcome the fossil fuel crisis. In this study, pyrolysis of bicycle and rickshaw tyres wastes was conducted and parametric effects (e.g., the effect of temperature, feed size and apparent vapor residence time etc.) on the pyrolysis product yields were determined. A fixed bed electric heating reactor was used for pyrolysis at 400 - 550 oC, maintaining various particles sizes and a constant heating rate of 20oC/min. The optimum Tyre Pyrolysis Oil (TPO) yield of 42 wt.% was obtained at 500 oC for a sample size of 4.0 cm3. The fuel properties (e.g., density, viscosity, calorific value, flash point, pour point, sulphur content, ash content etc.), functional group studies of the TPO were determined and was compared with the conventional fuel and with international standards. The physico-chemical properties of TPO confirm the use of TPO as furnace oil in various industrial processes. The fractionation of bio-oil gives various value added products including bio-gasoline, bio-kerosene and others chemicals. The commercial implementation of the pyrolysis and follow-up technologies for waste tires processing will allow energetic valorization of waste tyres in Bangladesh. Dhaka Univ. J. Sci. 70(2): 29-34, 2022 (July)